Web-Based Expert System For Respiratory Disorders In Human Using Backward Chaining Method - Rizal Rachman; Sandra Armayanti; Toni Kusnandar (LPPM STMIK Mardira Indonesia, 2023)
Respiratory disorders are various types of diseases or disorders that inhibit lung function. This disease can affect the ability to breathe. Respiratory disorders can be transmitted anytime and anywhere. Respiratory disorders are more common than other organ system disorders or infections. They start from the common cold with relatively mild to severe pneumonia, cough, fever, sore throat, and shortness of breath. Inadequate medical equipment also triggers the difficulty of treating and diagnosing a disorder. This study aims to help the community diagnose respiratory disorders and determine how to deal with them effectively and efficiently. This website-based expert system for diagnosing human respiratory disorders uses the Backward Chaining inference method. The results of this study will produce a website for diagnosing respiratory disorders in humans.